2013
DOI: 10.5694/mja13.10407
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and perceptions of overweight and obesity in Aboriginal and non‐Aboriginal young people in custody

Abstract: Overweight and obesity were highly prevalent but poorly recognised in young people in custody. A longer incarceration time had the strongest association with overweight obesity and self-reported weight gain. From a population health and policy perspective, changes to the liberal food environment and the approach to increasing physical activity in custody are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 13 publications
2
21
0
4
Order By: Relevance
“…Five studies assessed self‐reported change during incarceration ; four of these studies included adult participants . Four of these studies were conducted in Australia, and one study was conducted in the USA ; 84% of participants were younger than 18 years in the study by Haysom et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies assessed self‐reported change during incarceration ; four of these studies included adult participants . Four of these studies were conducted in Australia, and one study was conducted in the USA ; 84% of participants were younger than 18 years in the study by Haysom et al .…”
Section: Resultsmentioning
confidence: 99%
“…Four of these studies were conducted in Australia, and one study was conducted in the USA ; 84% of participants were younger than 18 years in the study by Haysom et al . . Four of these studies included participants from both genders (largely male); one study included adult male participants only .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dental caries is now the most common chronic disease of childhood in Australia, with a fourfold increase in dental caries between the ages of 12 and 21 years, predicting long‐term dental health and other diseases such as diabetes and cardiovascular disease . Incarcerated young people come from Aboriginal, rural and highly disadvantaged backgrounds, and are likely to suffer a greater share of poor oral health and the long‐term sequelae than their community peers . In addition, young people entering custody have very high rates of smoking, cannabis dependence and other substance use, which add to the burden of dental disease.…”
mentioning
confidence: 99%